PRINSIP DAN KARAKTERISTIK EKONOMI ISLAM PERSPEKTIF FIQH - Rahmad (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2022)
Islamic economics was born simultaneously with the birth of the teachings of Islam itself starting from the Prophet Muhammad SAW became an apostle. Economic activity in Islam is also considered as an activity that aims to serve oneself to Allah SWT. Therefore, its principles and characteristics are in line with the main guidelines of Muslims, namely the Qur'an and Hadith. The principles and characteristics of Islamic economics are formulated in such a way that the realization of happiness, peace, comfort and justice for economic actors without neglecting the right to develop themselves. The main goal of Islamic economics is to achieve falah or the fulfillment of needs and the creation of prosperity so as to give birth to happiness in the world and happiness in the Hereafter